Domestic time use among young people in Mexico and Costa Rica: a comparative study - Ortiz-Ávila, Elsa (2025)
Introduction: Gender differences in time use among adults are well documented worldwide; however, there is a clear gap regarding certain life stages, such as adolescence and young single adulthood. Objective: To study time use patterns by sex among the population aged 15 to 24 in two Latin American countries, Mexico and Costa Rica. The study also examines individual factors that may influence participation in these activities. Methodology: National time use surveys from Mexico (2019) and Costa Rica (2022) were analyzed to estimate indicators on domestic, paid, educational, caregiving, and leisure activities, as well as to fit Ordinary Least Squares (OLS) models. Results: Gender inequalities persist among the population aged 15 to 24 in Mexico and Costa Rica; women devote more time to domestic work, while men spend more time in paid employment. School and labor market participation reduce women’s domestic workload, but gaps remain, highlighting the influence of factors such as country and activity status in time use patterns. Conclusions: Women are systematically assigned domestic tasks from adolescence, contributing to the internalization of traditional gender roles and expectations.